Growth and Yield Models for Pinus halepensis Mill. - Montero, G.; Cañellas, I.; Ruíz-Peinado, R. (Forest Systems, 2001)
Growth and yield models of silviculture applied to four site indices have been drawn up. The data were obtained in 72 plots, installed in 1965 in man made stands of Pinus halepensis Mill., and inventoried in 1965, 1975, 1980, 1988 y 1999. The site index was defined as the top height at age 80 and models were adjusted using the Richards function, obtaining four site qualities: 20, 17, 14 and 11. Following this, silvicultural production models, including two different thinning regimes, were developed for the two higher site qualities sites, with more productive interest (20 and 17) using a simulation with the Hart-Becking rate. For 11 and 14 site quality, only one moderate thinning regime was developed, bearing in mind their most important protection value.